Middle Eocene astronomically-tuned benthic stable isotopes, bulk stable isotopes and Ca/Fe-ratios of IODP Expedition 342 Sites U1408 and U1410 - Maximilian Vahlenkamp; Simon D extquotesinglehaenens; David De Vleeschouwer; Pincelli M Hull; James C Zachos; Claudia Agnini; Heiko Pälike (PANGAEA, 2026)
To come to a coherent middle Eocene timescale for the Atlantic, we re-evaluate the astrochronology of chrons C20n/C20r at International Ocean Discovery Program (IODP) Expedition 342 Sites U1408 and U1410 off Newfoundland. Based on the stratigraphic work of Cappelli et al., 2019 a two-site-composite for the chrons C20n and C20r (~42-46 Ma) was constructed by transferring U1410 samples to the U1408 depth-scale. We then used previously published (U1410; Vahlenkamp et al., 2018) and new (U1408) benthic and bulk stable isotopes (d^13^C and d^18^O) to derive a revised eccentricity-tuned astrochronology for the Expedition 342 composite. The astrochronologic tuning demonstrates that the contourite deposition (reflected by the Ca/Fe ratio) at the Newfoundland Ridge occurred under an amplified climatic response to obliquity during C20n and C20r – with intermittent "astronomical flickering" to precession. To further test our astrochronology we refined nannofossil datums at Site 1263 to compare with those at Site U1410 (Cappelli et al., 2019). The new chronology synchronizes time scales across the Atlantic basin. A robust middle Eocene chronology for the North Atlantic is indispensable because Expedition 342 sites host the highest-resolution middle Eocene benthic stable isotope records for this time interval.